Transformational Leadership and Work Achievement LLDikti Lecturer, Region IX: The Role Of Empowerment Intervening - Muhammad Rusydi; Syarifuddin Sulaiman; Naidah Naidah (SEIKO : Journal of Management & Business, 2022)
Abstrak Research related to psychological empowerment is still very limited, so this study aims to find a model of pshychological empowerment of lecturers in improving work performance. The research instrument used a questionnaire with a sample of 196 respondents, the data was processed using SEM. The results show that transformational leadership influences empowerment and empowerment influences work performance, but transformational leadership has no significant effect on work performance. The transformational leadership through psychological empowerment can improve lecturers’ work performance. The novelty of this research lies in psychological empowerment as a framework for transformational leadership models in encouraging work performance among lecturers. Kata Kunci: Empowerment; Transformational leadership; Work performance.